2022
DOI: 10.4103/aja202232
|View full text |Cite
|
Sign up to set email alerts
|

An alternative surgical technique for varicoceles: a preliminary experience of the microsurgical spermatic (distal end)-inferior or superficial epigastric vein anastomosis in symptomatic varicoceles associated with perineal pain

Abstract: Many therapies are effective in treating varicoceles, including dilation of the pampiniform plexus in males. The most common method of treatment is varicocelectomy. We aimed to assess an alternative technique (microsurgical spermatic [distal end]-superficial or inferior epigastric vein anastomosis) that preserves the normal blood flow pattern for varicocele treatment. We retrospectively analyzed 27 men with varicocele between October 2019 and July 2020. All patients underwent microsurgical spermatic (distal en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The methods described by Wan et al . 1 and in our paper should probably not be done if the patient has venous reflux into the superficial epigastric vein (due to saphenofemoral incompetence), and previously mentioned series have also considered the possibility of the reflux into the deep inferior epigastric vein (in cases of iliac vein compression by the iliac artery). 3 This can be excluded by a preoperative Doppler examination.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…The methods described by Wan et al . 1 and in our paper should probably not be done if the patient has venous reflux into the superficial epigastric vein (due to saphenofemoral incompetence), and previously mentioned series have also considered the possibility of the reflux into the deep inferior epigastric vein (in cases of iliac vein compression by the iliac artery). 3 This can be excluded by a preoperative Doppler examination.…”
mentioning
confidence: 77%
“…This is useful when, during standard microsurgical varicocelectomy, the dissection of the internal spermatic veins around the artery is difficult, and the identification of the artery is uncertain. 2 As in Wan et al , 1 only dilated internal spermatic vein(s) are ligated and one is anastomosed to the superficial inferior epigastric vein. The rationale is that any persistent venous reflux (into the nonligated pampiniform veins) would be rerouted through the superficial epigastric vein, and will not reach the testicle due to higher vascular resistance ( ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with open inguinal or laparoscopic surgery, these methods have no advantages except for the esthetics of the skin incision after operation [32,34,36]. Other relevant studies have suggested that the new type of varicocele bypass vein anastomosis surgery is more aligned with human anatomy than venous embolism and can achieve etiological treatment [37]. However, it is still difficult to accurately judge the efficacy of bypass surgery and the standard of postoperative reexamination.…”
Section: Discussionmentioning
confidence: 99%